تحليل واقع الانفاق العام في ليبيا لأجل الترشيد والاصلاح خلال الفترة 2012 – 2019 - أ . عبدالرؤوف سعيد عبود (Aljameai, 2022)
الملخص:بهدف إبراز الدور الذي تلعبه السياسة الجيدة للمالية العامة للدولة في الحفاظ على الموارد المالية ومعرفة آليات ترشيد النفقات العامة تم اختيار التحليل النظري من خلال المنهج الوصفي التحليلي، وتم الاعتماد على المنهج الاستنباطي من خلال محاولة تعميم وإسقاط عوامل ومتطلبات كفاءة إدارة الإنفاق العام على سياسات ترشيد الإنفاق العام في ليبيا.ومن خلال عرض هيكلية النفقات العامة للدولة الليبية ودراسة تطورها لغرض تحديد ملامح السياسة المالية في ليبيا وتحليلها، يمكن استنتاج ان السياسة المالية العامة للدولة الليبية لم تسهم بكفاءة في الحفاظ على الموارد المالية ولم يتم انفاق المال العام بأسلوب يتسم بالرشاد.وينبغي تنفيذ تدابير الإصلاح وضبط أوضاع المالية العامة في جانب إدارة الموازنة، وفي جانب النفقات العامة، وفي جانب الإيرادات العامة.Abstract:order to highlight the role played by the good public financial policy of the state in preserving financial resources and knowing the mechanisms of rationalizing public expenditures, a theoretical analysis was chosen through the descriptive analytical approach, and the deductive approach was relied on by trying to generalize and drop the factors and requirements for the efficiency of public spending management on the rationalization policies. Public spending in Libya.By presenting the structure of the public expenditures of the Libyan state and studying its development for the purpose of defining and analyzing the features of the financial policy in Libya, it can be concluded that the public financial policy of the Libyan state did not efficiently contribute to the preservation of financial resources and public money was not spent in a rational manner.Reform and fiscal consolidation measures should be implemented on the budget management side, the public expenditure side, and the public revenue side.